Ergonomi dalam Narasi Visual: Analisis Workstation melalui Semiotika Ruang dan Waktu di Film Dimsum Martabak - Ahmad Riyadi Swandhani; Bintang Nugraha; Nur Sabariah; Sheila Andita Putri (LPPM STIKI Malang, 2025)
This study aims to analyze the use of ergonomics in the visual narrative of the film Dimsum Martabak through a spatial and temporal semiotics approach. Ergonomics, which focuses on the design and organization of optimal workspaces, has a significant impact on individual comfort and productivity within the work environment. The film, as a work of art, presents workspaces that function not only as places of physical interaction but also as mediums for communicating character dynamics and social relationships. The spatial and temporal semiotics approach is employed to explore how spatial elements in the film—such as layout and workstations—as well as the use of time in scenes, convey messages about ergonomics in everyday life. This analysis reveals how the film shapes viewers’ understanding of the importance of ergonomics within a broader visual context, and how workspace design can influence the physical and psychological well-being of the characters. The findings of this research are expected to contribute to a deeper understanding of how visual elements in film can reflect ergonomic conditions in real life.